Reproductive status of bluefin tuna during migration to Mediterranean spawning grounds through the Straits of Gibraltar - Medina A. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
The sexual maturation stage of adult bluefin tuna caught at the Strait of Gibraltar (Barbate) during migration to Mediterranean spawning grounds (Balearic Islands) was assessed by histological and stereological studies of the gonads. The gonad weight and gonadosomatic indices (GSI) of these tunas were lower than those of tuna from spawning grounds. The testes of migrant male tuna contained gametes at all stages of spermatogenesis; there were no marked histological differences, though the gonad size and GSI were higher in Balearic males. Most Barbate female bluefin tuna were non-spawning mature. The ovaries of Balearic spawning tuna contained 5-fold more vitellogenic oocytes than did Barbate tuna. The average fecundity per spawning in the Balearic specimens, estimated from stereological quantification of migratory-nucleus oocytes, was 13 million eggs (93 oocytes per g of body weight), and the inter-spawning interval was 1.2 days. These estimates are close to those calculated for other tuna species.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)